Penerapan Intervensi Audiovisual dalam Meningkatkan Kepatuhan Selama Proses Induksi Anestesi pada Anak yang Menjalani Tindakan Operasi - Noviyanti, Mita; Chodidjah, Siti; Rachmawati, Imami Nur (Journal of Telenursing (JOTING), 2024)
This study aims to evaluate the effectiveness of audiovisual intervention in enhancing compliance during anesthesia induction in children undergoing surgery. The methodology used is a systematic review of several English-language research articles published between 2014 and 2023. Articles were retrieved from five online databases, such as ProQuest, ScienceDirect, Scopus, Ebsco MEDLINE, and Embase. The results of this study demonstrated that the use of audiovisual intervention was effective in enhancing compliance during anesthesia induction in children undergoing surgery. In conclusion, audiovisual intervention can be implemented as part of preoperative preparation programs for children undergoing surgery in order to enhance their levels of compliance during anesthesia induction. Audiovisual interventions can be used to achieve positive postoperative outcomes, either when utilized alone or combined with standard perioperative care practices. Keywords:Audiovisual Intervention, Child, Surgery, Induction Compliance.